The development of environmental crime and sanction in Malaysia - Mustafa, Maizatun; Mohamed, Nurah Sabahiah (European Scientific Institute, 2015)
Environment and its resources are precious to human being and must be protected. Therefore, the continued degradation of the environment that happens mainly as a result of human activities ought to be subjected to regulatory control, and individuals or companies who willfully damage the environment ought to be punished. In Malaysia and elsewhere, environmental crimes continue to increase and extend to diverse areas including pollution, waste disposal, threats to flora, fauna and biodiversity,and illegal logging. Over the years, Malaysia’s changing perceptions about environmental vulnerability has altered the view on environmental crime. At present various strategies have been introduced to deal with different types of environmental offences, with laws that target not only individual offenders, but also make provision for corporate liability. This paper discusses in general the scope of environmental crimes in Malaysia, examines shifts in the regulation of environmental crime over the years since the passage of the Environmental Quality Act in 1974, and identifies the development of innovative strategies within the law in dealing with these crimes. The purpose of this paper is to document changes within the law on environmental crime that have shaped criminal law and environmental protection in Malaysia.